1964
DOI: 10.1677/joe.0.0300355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Hormones on the Tactile Sensitivity of the Canary Brood Patch

Abstract: 0\m=.\05 mg. oestradiol benzoate, injected thrice weekly alone or in combination with either 0\m=.\25 mg. progesterone or 75 i.u. prolactin, induced an increase in tactile sensitivity in the female canary's brood patch. Progesterone and prolactin alone did not produce this effect; 0\m=.\3 mg. of the oestrogen was also ineffective alone and in combination with the other hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 3 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…One possible means by which these hormones might enhance behavioral responses in the signal receiver is by modifying the way in which the receiver processes the signal. Such hormone-dependent modification of signal processing occurs in several vertebrates, including humans [Hinde and Steele, 1964;Komisaruk et al, 1972;Wright and Crow, 1973;Elkind-Hirsch et al 1992;Penna et al, 1992;Sisneros et al, 2004;Wal-purger et al, 2004;Maney et al, 2006; see Zakon and Smith, 2002, for review], and such plasticity might even serve as an adaptable mechanism by which communication between sender and receiver is improved during the breeding season [Sisneros et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…One possible means by which these hormones might enhance behavioral responses in the signal receiver is by modifying the way in which the receiver processes the signal. Such hormone-dependent modification of signal processing occurs in several vertebrates, including humans [Hinde and Steele, 1964;Komisaruk et al, 1972;Wright and Crow, 1973;Elkind-Hirsch et al 1992;Penna et al, 1992;Sisneros et al, 2004;Wal-purger et al, 2004;Maney et al, 2006; see Zakon and Smith, 2002, for review], and such plasticity might even serve as an adaptable mechanism by which communication between sender and receiver is improved during the breeding season [Sisneros et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Furtherm ore, after castration the decline of sexual activity is not necessarily correlated with the morphological change in glans penis [Aronson and Cooper, 1967;Beach and Westbrook, 1968]. However, in females, except for a few reports [Herren, 1933;Hinde and Steel, 1964] that indicate a hor monal effect on peripheral sensory systems, the m atter has not been extensively investigated.…”
mentioning
confidence: 99%
“…Estrogen treatment alone, rather than progesterone or estrogen with progesterone, was chosen for the investigation because it has been reported that progesterone does not have a peripheral sensory effect [Hinde and Steel, 1964], In female rats, estrogen alone can induce estrous behavior [Davidson et at., 1968;Peaff, 1970a], The area of skin chosen for study was the perineal region of the female rat, which is innervated by a branch of the pudendal nerve. Film study of female rat sexual behavior has shown that this area of skin is touched by the male rat during copulation [Pfaff, 1970b[Pfaff, , 1971.…”
mentioning
confidence: 99%
“…The brood patch was examined, and its tactile threshold assessed, on the 4 days preceding the first injection, and five times a week thereafter for 3 weeks. The rating scales used for defeathering and vascularity are given by , and the method for assessing the tactile sensitivity by Hinde & Steel (1964).…”
Section: Methodsmentioning
confidence: 99%